2020
DOI: 10.1002/jmv.25698
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatics‐aided identification of T cell and B cell epitopes in the surface glycoprotein of 2019‐nCoV

Abstract: The 2019 novel coronavirus (2019-nCoV) outbreak has caused a large number of deaths with thousands of confirmed cases worldwide, especially in East Asia.This study took an immunoinformatics approach to identify significant cytotoxic T lymphocyte (CTL) and B cell epitopes in the 2019-nCoV surface glycoprotein. Also, interactions between identified CTL epitopes and their corresponding major histocompatibility complex (MHC) class I supertype representatives prevalent in China were studied by molecular dynamics si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
273
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(310 citation statements)
references
References 26 publications
11
273
1
4
Order By: Relevance
“…The interactions between these epitopes and their corresponding MHC class I molecules were studied further by using molecular dynamics simulations and found that the CTL epitopes bind with MHC class I peptide-binding grooves via multiple contacts, thus indicating their potential for generating immune responses. 30 Such epitopes may possess the ideal characteristics to become part of COVID-19 vaccine candidates. The nucleocapsid (N) protein as well as the potential B cell epitopes of the E protein of MERS-CoV has been suggested as probable immunoprotective targets that induce both T-cell and neutralizing antibody responses.…”
Section: Vaccinesmentioning
confidence: 99%
“…The interactions between these epitopes and their corresponding MHC class I molecules were studied further by using molecular dynamics simulations and found that the CTL epitopes bind with MHC class I peptide-binding grooves via multiple contacts, thus indicating their potential for generating immune responses. 30 Such epitopes may possess the ideal characteristics to become part of COVID-19 vaccine candidates. The nucleocapsid (N) protein as well as the potential B cell epitopes of the E protein of MERS-CoV has been suggested as probable immunoprotective targets that induce both T-cell and neutralizing antibody responses.…”
Section: Vaccinesmentioning
confidence: 99%
“…As the analysis of protein sequences has shown, eight HLA-DR epitopes that are located in the Spike, Envelope, and Membrane of the 2019-nCoV play an essential part in the obstruction of the immune surveillance [29]. Also, there are B-cell and cytotoxic T lymphocyte epitopes that are uniquely present on the surface glycoprotein of 2019-nCoV [36]. These epitopes are likely a vaccine target for the 2019-nCoV.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The identification of B-cell and T-cell epitopes for SARS-COV-2 proteins is critical for the development of effective diagnostic tests and vaccine, especially for structural N and S proteins, which had been predicted by bioinformatics 19,20 . For example, there are several RT-PCR tests for detecting COVID-19 that target the S or N protein genome 21 .…”
Section: Textmentioning
confidence: 99%